Protection of Mono and Polyunsaturated Fatty Acids from Grapeseed Oil by Spray Drying Using Green Biopolymers as Wall Material (2022)
ABSTRACT: One of the most common ways to protect oils is microencapsulation, which includes the use of encapsulating agents. Due to the environmental problems facing humanity, this study seeks to combine green biopolymers (microcrystalline cellulose and whey protein isolate) that function as encapsulating agents for grapeseed oil. Grapeseed oil that is obtained from agro-industrial waste has shown health benefits, including cardioprotective, anticancer, antimicrobial, and antiinflammatory properties. These health benefits have been mainly associated with monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids. In this sense, it has been observed that grapeseed oil can be easily modified by environmental factors such as oxygen, high temperatures, and light, showing the instability and easy degradation of grapeseed oil. In this study, grapeseed oil was encapsulated using the spray-drying technique to conserve its lipidic profile. Powder recovery of the grapeseed oil microcapsules ranged from 65% to 70%. The encapsulation efficiency of the microcapsules varied between 80% and 85%. The FTIR analysis showed chemical interactions that demonstrate chemisorption between the grapeseed oil and the encapsulating material, while the SEM micrographs showed a correct encapsulation in a spherical shape. Gas chromatography showed that the lipid profile of grapeseed oil is preserved thanks to microencapsulation. Release tests showed 80% desorption within the first three hours at pH 5.8. Overall, whey protein and microcrystalline cellulose could be used as a wall material to protect grapeseed oil with the potential application of controlled delivery of fatty acids microcapsules.